Pengaruh Pengelolaan Pembiayaan Agunan Rumah terhadap Peningkatan Nasabah PT. Bank Syari’ah Mandiri (Persero) Kantor Cabang Pembantu Kedaton Bandar Lampung - Apun Syaripudin; Miftahur Rohman (Universitas Mitra Indonesia, 2020)
In the concept of Shariah and conventional perbankkan is equally serves as a financial intermediary so many different products perbankkan sharia is not a product with conventional banks . The purpose of this study was to determine and analyze the effect of home mortgage financing management to increase customer at PT . Sharia Bank Mandiri ( Persero ) Branch Office Kedaton Bandar Lampung . While desaian research used in this paper is a qualitative analysis . Based on the results it can be seen that : ( 1 ) The management of home ownership through Musharaka financing at Bank Syariah Mandiri ( Persero ) Branch Office Kedaton Bandar Lampung is good enough is evident from the implementation of financing the management of home ownership that does not burden the bank's customers and always strive for improvement -Fixes lease quickly if the object is not in accordance with the wishes of the customer . ( 2 ) The management of home ownership through Ijara financing of Bank Syariah Mandiri ( Persero ) Branch Office Kedaton Bandar Lampung has done fairly well in accordance with the provisions of sharia perbankkan .